Kurikulum Muatan Lokal Keagaman dalam Membentuk Budaya Religius : Studi Kasus di SMP Islam Raudlatul Ulum Brangkal Bandar Kedungmulyo Jombang - Farihah, Abidah Lailatul; Umam , Khoirul; Mutmainnah Sari, Rofika (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
The curriculum is one important component that is crucial in the unit of the education system, To achieve goals and good results an education will not succeed without a good curriculum. The curriculum of local religious content is expected to be able to produce perfect faith, perfect piety, good morals, and active in building civilization and harmony of life. This study aims to determine how the implementation of the local religious content curriculum in shaping religious culture. Through learning local religious content can improve the quality of religion and develop cognitive values and psychomotor values of students. The methodology in this study uses a qualitative approach and type of case study research by collecting data from observations, interviews, and documentation. In analyzing the data using Milles and Huberman's data analysis. The results show that the curriculum of local religious content in shaping students' religious culture is that it has lasted for 4 years. The material taught in the local religious content curriculum is more on material that hones the religious skills of students. The material taught includes the fields of prayer, BTQ, Worship, and prayer, as well as memorization of the letters. there are several ways including regulations and making programs carried out in schools, and maximizing religious symbols and realized in religious application programs. This program is the result of the development of extracurricular activities in the curriculum of local religious content. also develops learning outcomes or learning outcomes for local religious content.